A kind of oxygen evolution catalyst for PEM water electrolysis and its preparation method and use
By introducing TiN support to the IrRu catalyst for co-doping, the problem of insufficient catalyst activity and stability is solved, and a low-cost and high-stability catalytic effect is achieved, which is suitable for large-scale industrial applications.
Patent Information
- Application Number
- CN202410993012.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-24
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-07-24
AI Technical Summary
The existing IrRu catalysts have insufficient activity and stability, high costs, and are difficult to meet the needs of large-scale industrial applications.
TiN is used as a support to form co-doping with Ir ions and Ru ions, reducing the oxidative dissolution of IrO2 and RuO2, inhibiting the agglomeration of metal oxide particles, thereby improving the activity and stability of the catalyst.
It significantly improves the catalytic activity and stability of IrRu catalyst, reduces the amount of precious metals, and achieves a low-cost and high-stability catalytic effect. The catalyst can operate stably for more than 3,000 hours under the action of a large current.
Smart Images

Figure CN118563359B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of electrocatalytic water electrolysis, and specifically relates to a noble metal-loaded oxygen evolution catalyst, a preparation method thereof, and application of the catalyst in PEM (proton exchange membrane) water electrolysis. Background Art
[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.
[0003] PEM electrolysis technology has the advantages of high energy conversion efficiency, compact size, fast response speed, and the ability to produce high-purity and high-pressure hydrogen. PEM electrolysis technology is more suitable for water electrolysis coupled with renewable energy generation to produce hydrogen. Among them, oxygen evolution catalyst is the key to affecting the rate of PEM water electrolysis.
[0004] The rate of water electrolysis is limited by the four-electron characteristics of the oxygen evolution reaction. IrO2 (iridium dioxide) and RuO2 (ruthenium dioxide) are rutile oxides that have good oxygen evolution catalytic activity under strong acidic conditions. Among them, RuO2 has the highest activity, but it is easy to dissolve in an acidic environment and has poor stability. IrO2 has good stability and its oxygen evolution activity is second only to RuO2. Iridium and ruthenium are compounded to form a rutile IrO2-RuO2 solid solution, which can show high oxygen evolution activity and stability at the same time. However, the scarcity and high price of iridium and ruthenium hinder the large-scale industrial application of hydrogen production. Therefore, it is crucial to design new water electrolysis catalysts with excellent activity, low cost and high stability.
[0005] Some studies have successfully synthesized RuO2NPs / TiN electrocatalysts by depositing RuO2 nanoparticles (NPs) on TiN (titanium nitride) nanotubes, and improved the stability of the ruthenium base by introducing a stable carrier. However, the issue of improving the activity and stability of IrRu (iridium ruthenium) catalysts (with RuO2 and IrO2 as active components) has not been addressed.
[0006] In summary, there are many methods to improve the activity and stability of catalysts, such as hybridization with metals, introduction of stable carriers, chemical doping or formation of solid solutions, but no method has been found to significantly improve the catalytic activity and stability of IrRu catalysts.
[0007] In view of this, the present invention is proposed. Summary of the invention
[0008] The technical problem to be solved by the present invention is to overcome the defects of poor activity, low life and high cost of existing catalysts, and provide an oxygen evolution catalyst for PEM water electrolysis and a preparation method and use. The present invention has found that using TiN as a carrier to form co-doping with Ir ions and Ru ions can reduce the oxidative dissolution of IrO2 and RuO2, inhibit the agglomeration of metal oxide particles during the catalytic process, and thus significantly improve the catalytic activity and stability of the IrRu catalyst.
[0009] The present invention loads precious metals on TiN to reduce the amount of precious metals used and achieve the purpose of reducing costs. Since TiN partially fills the Ti-3d orbital (titanium's 3d orbital) and is not completely hybridized with the N-2p (nitrogen's 2p orbital) electrons, TiN exhibits high electronic conductivity and excellent stability. When TiN is used as a carrier and doped with Ir ions and Ru ions, the electron transfer of TiN to IrO2@RuO2 reduces the d-band center and weakens the oxidative dissolution of IrO2 and RuO2, thereby reducing costs and improving the electrochemical stability of the catalyst. While introducing the TiN carrier, the agglomeration of metal oxide particles during the catalytic reaction is suppressed, and the specific active sites of the active material are increased, thereby increasing the mass specific activity of the precious metal, thereby increasing the utilization rate of the precious metal in the catalyst. While suppressing the agglomeration of active substances and improving the activity of the catalyst, the present invention also improves the stability of the catalyst. The catalyst prepared by the present invention has a high conductivity at 1A / cm 2 Under the action of large current, it can run stably for more than 3,000 hours.
[0010] In order to achieve the above object, the present invention adopts the following technical solution:
[0011] The first aspect of the present invention provides an oxygen evolution catalyst for PEM water electrolysis, comprising: a carrier and a precious metal active component, wherein the precious metal active component is loaded on the carrier, and the carrier is titanium nitride; the precious metal active component is a mixture of IrO2 and RuO2; the carrier accounts for 20%-60% of the total mass of the catalyst.
[0012] Furthermore, the size of the titanium nitride is 20nm-100nm. It should be noted that when the size of the titanium nitride carrier is less than 100nm, due to the small size of the carrier, there are more exposed active sites, the catalytic activity is better after loading the precious metal, and the electrochemical stability is significantly improved; when the size of the titanium nitride is less than 20nm, the cost increases, which violates the original intention of reducing costs.
[0013] Furthermore, the carrier accounts for 30%-40% of the total mass of the catalyst.
[0014] Furthermore, the mass ratio of IrO2 to RuO2 is 1:0.25-1.5. When RuO2 is used for PEM water electrolysis, soluble high-valent metal ions will be formed under acidic oxygen evolution reaction conditions and with a high oxidation potential, and the dissolution of active substances will lead to poor electrochemical stability. The present invention forms a synergistic effect by compounding IrO2 and RuO2 in a mass ratio of 1:(0.25-1.5), while retaining the excellent activity of ruthenium and the high stability of iridium, and reducing the dissolution of active substances. When the mass ratio of IrO2 to RuO2 is not within the range of 1:(0.25-1.5), the synergistic effect is not obvious.
[0015] The second aspect of the present invention also provides a method for preparing an oxygen evolution catalyst for PEM water electrolysis, comprising:
[0016] Dissolving an iridium-containing compound and a ruthenium-containing compound in water, and adjusting the pH to 9-10 under stirring to obtain a noble metal precursor solution;
[0017] The titanium nitride powder is mixed with concentrated hydrochloric acid having a mass concentration of 36 wt% to 38 wt%, and heated under stirring to obtain a titanium nitride carrier;
[0018] The titanium nitride carrier is dispersed in an organic solvent, and the noble metal precursor solution is added to react. After the reaction is completed, the titanium nitride carrier is centrifuged, washed, and dried to obtain the product.
[0019] Furthermore, the iridium-containing compound is chloroiridic acid or iridium trichloride hydrate. The ruthenium-containing compound is ruthenium trichloride. The method provided by the present invention can ensure that iridium and ruthenium can be well complexed before loading to form a more stable complex, thereby improving the catalytic activity and stability of the catalyst.
[0020] Furthermore, sodium hydroxide or ammonia water is used to adjust the pH.
[0021] Furthermore, the heating treatment condition is 65°C-70°C for 0.5h-1h.
[0022] Furthermore, the reaction temperature is 160°C-180°C, and the reaction time is 2h-4h.
[0023] The third aspect of the present invention also provides the use of the above-mentioned oxygen evolution catalyst for PEM water electrolysis in hydrogen production by PEM water electrolysis.
[0024] Beneficial Effects of the Invention
[0025] (1) The present invention provides a catalyst of iridium and ruthenium bimetallic supported on titanium nitride, which exhibits high catalytic activity and excellent stability under the action of large current, and has the advantage of low cost. Compared with the existing IrRu catalyst, the catalyst provided by the present invention has obvious cost advantages; compared with the existing single precious metal supported catalyst, the catalyst provided by the present invention reduces the amount of precious metal used and has excellent catalytic activity and stability. Therefore, the catalyst provided by the present invention is easier to achieve large-scale industrial application.
[0026] (2) The catalyst preparation method provided by the present invention is simple, the prepared catalyst is uniformly loaded and dispersed, the preparation is stable and the yield is high (yield is about 94%-97%), and large-scale industrial preparation is easy to achieve.
[0027] (3) The preparation method of the present invention is simple, practical and easy to promote. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention, and the exemplary embodiments of the present invention and their description are used to explain the present invention and do not constitute improper limitations on the present invention.
[0029] Figure 1 is the XRD spectrum of the catalyst prepared in Example 1 of the present invention and Comparative Example 2;
[0030] Figure 2 It is a comparison chart of OER curves of catalysts prepared in Example 1, Example 4, Example 7 of the present invention and Comparative Example 1, Comparative Example 2, Comparative Example 3;
[0031] Figure 3 is a polarization curve diagram of the PEM electrolyzer of the present invention;
[0032] Figure 4 is 1A / cm 2 The stability test results of the catalyst of the present invention under current density. DETAILED DESCRIPTION
[0033] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.
[0034] Terminology explanation:
[0035] In the present invention, the "IrRu catalyst" is a catalyst containing Ir element and Ru element, and its precious metal active components are IrO2 and RuO2.
[0036] In the present invention, "Ir catalyst" refers to pure iridium black as a catalyst.
[0037] The present invention will be further described in detail below in conjunction with specific embodiments. It should be noted that the specific embodiments are intended to explain the present invention rather than to limit it.
[0038] In the following examples, each particle size is an average particle size.
[0039] Embodiment 1:
[0040] Take 0.58g of iridium trichloride hydrate and 0.43g of ruthenium chloride and dissolve them in 40mL of deionized water. Under stirring, add ammonia water to adjust the pH to 9 to obtain a precious metal precursor solution; mix 0.5g of 20nm titanium nitride powder with 100mL of concentrated hydrochloric acid (36wt%), stir and treat at 65°C for 1h, collect solid particles and dry them to obtain a titanium nitride carrier; take 0.1g of the titanium nitride carrier, add it to 200mL of ethylene glycol, and perform ultrasonic dispersion treatment; add the prepared precious metal precursor solution to the above ethylene glycol and stir evenly, heat to 165°C to react for 3h, wash with deionized water and centrifuge several times, then dry in vacuo at 60°C, and finally obtain 0.506g of the product catalyst.
[0041] The oxygen evolution catalyst for PEM water electrolysis described in Example 1, wherein the carrier is 20nm titanium nitride, the mass percentage of the carrier is 20%, and the mass ratio of the precious metal active components IrO2 and RuO2 is 1:0.25.
[0042] Embodiment 2:
[0043] The method is the same as in Example 1, except that the selected carrier is 50 nm titanium nitride, the mass percentage of the catalyst carrier is 20%, and the mass ratio of the precious metal active components IrO2 and RuO2 is 1:0.25.
[0044] Embodiment 3:
[0045] The method is the same as in Example 1, except that the carrier used is 100 nm titanium nitride, the mass percentage of the catalyst carrier is 20%, and the mass ratio of the precious metal active components IrO2 and RuO2 is 1:0.25.
[0046] Embodiment 4:
[0047] Take 1g of chloroiridic acid and 0.43mg of ruthenium chloride and dissolve them in 40mL of deionized water. Under stirring, add ammonia water to adjust the pH to 9 to obtain a precious metal precursor solution; mix 0.5g of 50nm titanium nitride powder with 100mL of concentrated hydrochloric acid (36wt%), stir and treat at 70℃ for 0.5h, collect solid particles and dry them to obtain a titanium nitride carrier; take 0.18g of the titanium nitride carrier, add it to 200mL of ethylene glycol, and perform ultrasonic dispersion treatment; add the prepared precious metal precursor solution to the above ethylene glycol and stir evenly, heat to 160℃ to react for 4h, wash with deionized water and centrifuge several times, then dry in vacuo at 60℃, and finally obtain 0.6g of the product catalyst.
[0048] The oxygen evolution catalyst for PEM water electrolysis described in Example 4, wherein the carrier is 50nm titanium nitride, the mass percentage of the carrier is 30%, and the mass ratio of the precious metal active components IrO2 and RuO2 is 1:0.25.
[0049] Embodiment 5:
[0050] The method is the same as that of Example 4, except that the selected carrier titanium nitride is 0.28 g. The catalyst carrier is 50 nm titanium nitride, the mass percentage of the catalyst carrier is 40%, and the mass ratio of the precious metal active components IrO2 and RuO2 is 1:0.25.
[0051] Embodiment 6:
[0052] The method is the same as that of Example 4, except that the selected carrier titanium nitride is 0.65 g. The catalyst carrier is 50 nm titanium nitride, the catalyst carrier mass percentage is 60%, and the mass ratio of the precious metal active components IrO2 and RuO2 is 1:0.25.
[0053] Embodiment 7:
[0054] The method is the same as Example 4, except that the amount of precious metal used is 0.81g of chloroiridic acid and 0.79g of ruthenium chloride. The catalyst carrier is 50nm titanium nitride, the catalyst carrier mass percentage is 30%, and the mass ratio of the precious metal active components IrO2 and RuO2 is 1:0.5.
[0055] Embodiment 8:
[0056] The method is the same as Example 4, except that the amount of precious metal used is 0.608g of chloroiridic acid and 1.187g of ruthenium chloride. The catalyst carrier is 50nm titanium nitride, the catalyst carrier mass percentage is 30%, and the mass ratio of the precious metal active components IrO2 and RuO2 is 1:1.
[0057] Embodiment 9:
[0058] The method is the same as Example 4, except that the amount of precious metal used is 0.49g of chloroiridic acid and 1.425g of ruthenium chloride. The catalyst carrier is 50nm titanium nitride, the catalyst carrier mass percentage is 30%, and the mass ratio of the precious metal active components IrO2 and RuO2 is 1:1.5.
[0059] Embodiment 10:
[0060] Take 0.81g of chloroiridic acid and 0.79g of ruthenium chloride and dissolve them in 40mL of deionized water. Under stirring, add sodium hydroxide to adjust the pH to 10 to obtain a precious metal precursor solution; mix 0.5g of 100nm titanium nitride powder with 100mL of concentrated hydrochloric acid (38wt%), stir and treat at 70°C for 0.5h, collect solid particles and dry them to obtain a titanium nitride carrier; take 0.28g of the titanium nitride carrier, add it to 200mL of ethylene glycol, and perform ultrasonic dispersion treatment; add the prepared precious metal precursor solution to the above ethylene glycol and stir evenly, heat to 180°C to react for 2h, wash with deionized water and centrifuge several times, then dry in vacuo at 60°C to finally obtain 0.7g of the product catalyst.
[0061] The oxygen evolution catalyst for PEM water electrolysis described in Example 10, wherein the carrier is 50nm titanium nitride, the mass percentage of the carrier is 40%, and the mass ratio of the precious metal active components IrO2 and RuO2 is 1:0.5.
[0062] Comparative Example 1:
[0063] 1 g of chloroiridic acid was dissolved in 40 mL of deionized water to obtain a noble metal precursor solution; then it was added into 200 mL of ethylene glycol, stirred and heated to 165°C for reaction for 3 h, washed with deionized water and centrifuged several times, and dried in vacuo at 60°C to finally obtain the product catalyst.
[0064] The catalyst described in Comparative Example 1 uses pure iridium black as the catalyst.
[0065] Comparative Example 2:
[0066] Take 1g of chloroiridic acid and 0.43mg of ruthenium chloride and dissolve them in 40mL of deionized water. Under stirring, add ammonia water to adjust the pH to 9 to obtain a precious metal precursor solution; then add it to 200mL of ethylene glycol, stir and heat to 165℃ to react for 3h, wash with deionized water and centrifuge several times, and finally dry it in a vacuum at 60℃ to obtain the product catalyst.
[0067] The catalyst described in Comparative Example 2 uses IrRu as the catalyst. The mass ratio of the noble metal active components IrO2 to RuO2 is 1:0.25.
[0068] Comparative Example 3:
[0069] 1 g of chloroiridic acid was dissolved in 40 mL of deionized water to obtain a noble metal precursor solution; 0.5 g of 50 nm titanium nitride powder was mixed with 100 mL of concentrated hydrochloric acid (36 wt%), and stirred at 70 ° C for 0.5 h, and solid particles were collected and dried to obtain a titanium nitride carrier; 0.16 g of the titanium nitride carrier was added to 200 mL of ethylene glycol and subjected to ultrasonic dispersion treatment; the diluted noble metal precursor solution was added to the above ethylene glycol, stirred evenly, and heated to 165 ° C for reaction for 3 h, washed with deionized water and centrifuged several times, and dried in vacuo at 60 ° C to finally obtain the product catalyst.
[0070] The catalyst described in Comparative Example 3 uses iridium-supported titanium nitride as the catalyst, and the mass percentage of the titanium nitride carrier is 30%.
[0071] Comparative Example 4
[0072] The difference from Example 4 is that titanium dioxide is used instead of titanium nitride as the catalyst carrier.
[0073] Comparative Example 5
[0074] The difference from Example 4 is that molybdenum nitride is used instead of titanium nitride as the catalyst carrier.
[0075] Comparative Example 6
[0076] The difference from Example 4 is that tin dioxide is used instead of titanium nitride as the catalyst carrier.
[0077] The catalysts prepared in Example 1 and Comparative Example 2 were characterized, and the XRD patterns were as follows: Figure 1 As shown;
[0078] The catalysts prepared in Example 1, Example 4, Example 7 and Comparative Example 1, Comparative Example 2, Comparative Example 3 were subjected to initial electrochemical performance tests in a 0.1M HClO4 (perchloric acid) solution saturated with N2, and the catalyst loading was 0.2 mg / cm 2 , the test results are as follows Figure 2 shown.
[0079] The IrRu / TiN catalysts prepared in Examples 1, 4, and 7, the iridium black catalyst prepared in Comparative Example 1, the IrRu catalyst prepared in Comparative Example 2, and the Ir / TiN catalyst prepared in Comparative Example 3 were used as anodes to electrolyze water to produce hydrogen in a PEM electrolyzer. The spraying loading was 1 mg / cm 2 ; The cathode catalyst is 40wt.%Pt / C, and the Pt (platinum) loading is 0.4mg / cm 2 , DuPont 115 membrane, electrode area 45cm 2 , the test temperature is 60℃, the polarization curve of PEM electrolyzer is as follows Figure 3 shown.
[0080] At 1A / cm 2 The stability test of the catalyst prepared in Example 1 was carried out under a current density of 1000 nm. The catalyst prepared in Example 1 was used as the anode and the spraying loading was 1 mg / cm 2 ; The cathode catalyst is 40wt.%Pt / C, and the Pt loading is 0.4mg / cm 2 , DuPont 115 membrane, electrode area 45cm 2 The test temperature is room temperature. Heat is generated during electrolysis in the electrolytic cell. The water temperature is about 40°C. The test results are as follows: Figure 4 shown.
[0081] Test overpotential: 10mA / cm 2 Overpotential value of the catalyst under current density. Test growth potential: 10mA / cm 2 The potential increase of the catalyst under 20h continuous testing at the current density is shown in Table 1.
[0082] Table 1 Specific parameters of the examples and comparative examples
[0083]
[0084] From the comparison between Example 4 and Comparative Examples 1-3, it can be seen that the introduction of the TiN carrier effectively improves the catalytic activity and stability compared with the Ir catalyst or the IrRu catalyst; at the same time, the effect of the TiN carrier on improving the catalytic activity and stability of the IrRu catalyst is significantly better than that on the Ir catalyst.
[0085] From the comparison between Example 4 and Comparative Examples 4-6, it can be seen that, compared with other carriers, using TiN as a carrier for co-doping with IrRu can better improve the catalytic activity and stability of the catalyst.
[0086] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. An oxygen evolution catalyst for PEM water electrolysis, characterized in that: include: A carrier and a noble metal active component, wherein the noble metal active component is loaded on the carrier, and the carrier is titanium nitride; the noble metal active component is a mixture of IrO2 and RuO2; the carrier accounts for 20%-60% of the total mass of the catalyst; The mass ratio of IrO2 to RuO2 is 1:0.25-1.5; The IrO2 and RuO2 are compounded to form a synergistic effect; The PEM water electrolysis oxygen evolution catalyst 1A / cm 2 Under the action of large current, it can run stably for more than 3,000 hours.
2. The oxygen evolution catalyst for PEM water electrolysis according to claim 1, characterized in that The size of the titanium nitride is 20nm-100nm.
3. The oxygen evolution catalyst for PEM water electrolysis according to claim 1, characterized in that: The carrier accounts for 30%-40% of the total mass of the catalyst.
4. A method for preparing an oxygen evolution catalyst for PEM water electrolysis according to any one of claims 1 to 3, characterized in that: include: Dissolving an iridium-containing compound and a ruthenium-containing compound in water, and adjusting the pH to 9-10 under stirring to obtain a noble metal precursor solution; The titanium nitride powder is mixed with concentrated hydrochloric acid having a mass concentration of 36 wt% to 38 wt%, and heated under stirring to obtain a titanium nitride carrier; The titanium nitride carrier is dispersed in an organic solvent, and the noble metal precursor solution is added to carry out a reduction reaction. After the reaction is completed, the titanium nitride carrier is centrifuged, washed, and dried to obtain the product.
5. The method for preparing an oxygen evolution catalyst for PEM water electrolysis according to claim 4, characterized in that: The iridium-containing compound is chloroiridic acid or iridium trichloride hydrate, and the ruthenium-containing compound is ruthenium trichloride.
6. The method for preparing an oxygen evolution catalyst for PEM water electrolysis according to claim 4, characterized in that: The pH was adjusted with sodium hydroxide or ammonia.
7. The method for preparing an oxygen evolution catalyst for PEM water electrolysis according to claim 4, characterized in that: The heating treatment condition is 65°C-70°C for 0.5h-1h.
8. The method for preparing an oxygen evolution catalyst for PEM water electrolysis according to claim 4, characterized in that: The temperature of the reduction reaction is 160° C.-180° C., and the reaction time is 2 h-4 h.
9. Use of the oxygen evolution catalyst for PEM water electrolysis as claimed in any one of claims 1 to 3 in PEM water electrolysis to produce hydrogen.
Citation Information
Patent Citations
Catalyst for PEM water electrolysis, preparation method and application thereof
CN114395779A